EP712 Ovarian borderline tumors with invasive peritoneal implants: a long term follow-up study of 30 patients. (1st November 2019) - Gaichies, L; Maulard, A; Genestie, C; Pautier, P; Bentivegna, E; Leary, A; Chargari, C; Morice, P; Gouy, S
Abstract : Introduction/Background: Ovarian serous borderline tumors with invasive peritoneal implants (SBOT-IPI) are associated with serous low grade carcinomas (SLGC) in the 2016 WHO classification of ovarian neoplasms. Even if SBOT-IPI can relapse as SLGC in 30% of cases, long term survival is not well known. The aim of this study was to describe the frequency and the characteristics of the recurrences of OSBT-IPI. Methodology: Retrospective study of patients referred to our institution, from 1971 to 2018, for a SBOT-IPI with a minimal follow-up of 12 months. Results: 30 patients were identified; the median age at diagnosis was 36, 5 [19–72] year. FIGO stage was up to IIIA for 26 patients and the average number of peritoneal areas involved was 4, 5 [1–12]. The median follow-up was 106, 6 [12–366] months. Twelve patients (40%) developed an invasive relapse (4 as SBOT-IPI and 7 as SLGC) with an average time of 53, 6 [10, 1–175, 8] months. In this group, the mean age was 45, 3 [23–72] year old at first diagnosis. The initial stage was up to IIIB in 75% of the cases and the average number of peritoneal areas involved was 5, 2 [1–12]. Two patients died due to recurrence, one had a recurrence as SBOT-IPI 6 years after and one as SLGC 10 years after. Conclusion: Relapsing as an invasive disease were more frequent than reported in other series and seems to be associated with the initial FIGO stage and with the number of peritoneal areas involved in the initial diagnosis. However, in this long term follow-up study, overall mortality of SBOT-IPI seems lower than mobility rate of SLGC. This study highlights that SBOT-IPI long term survival is poorly known. Finally, the prognosis of the SBOT-IPI should not be associated with the SLGC. Disclosure: Nothing to disclose.